Comparison of the median and ulnar nerves of rheumatoid arthritis patients and healthy subjects by ultrasound - Çiğdem Atan Uzun; İsmihan Sunar and Zafer Günendi and Feride Nur Göğüş (Archives of Rheumatology, 2023)
Objectives: In this study, we aimed to investigate ulnar and median nerve cross-sectional areas (CSAs) by ultrasonography in RA patients who had no signs or symptoms of neurologic involvement. Patients and methods: This case-control study was conducted with 76 participants (72 females, 4 males; mean age: 53.2+10.9 years; range, 18 to 65 years) between April 2011 and April 2013. Of the participants, 38 were RA patients without any signs or symptoms of ulnar or median nerve involvement, and 38 were healthy subjects. All participants were evaluated with ultrasound. The median and ulnar nerve CSAs were measured at the proximal inlet of the carpal tunnel using the pisiform bone as a landmark. Results: There were no statistically significant differences between patients and controls in terms of median and ulnar CSAs (p>0.05). There were no correlations between median and ulnar CSAs of the dominant hand and age, height, weight, and disease duration. The median nerve CSA was >10 mm2 in 24% of the RA patients and 14% of controls, but the difference was not statistically significant (p=0.20). Conclusion: Similar median and ulnar CSAs were detected in RA patients and healthy controls. These findings cannot rule out a subclinical neurologic involvement.